On some species of Zygophylax Quelch, 1885 (Cnidaria: Hydrozoa: Zygophylacidae) from off New Caledonia - Galea, Horia R.; Maggioni, Davide; Galli, Paolo (Zootaxa, 2022)
Eleven species of hydroids belonging to the genus Zygophylax Quelch, 1885 are present in the material collected by the KANACONO, KANADEEP and KANADEEP 2 expeditions of the French Tropical Dee-Sea Benthos Program. Of these, ten represent known taxa and are fertile specimens, while the last one is unidentifiable in the absence of its gonosome. Seven species are new records for the study area. Zygophylax dispersa Peña Cantero, 2020 is assigned to the synonymy of Z. pseudafricana Vervoort & Watson, 2003, while Z. laertesi Peña Cantero, 2020 is comprehensively redescribed based on numerous and morphologically-varied specimens. Uncertainties exist as to the synonymy between Z. antipathes (Lamarck, 1816) and Z. rufa (Bale, 1884), but the oldest available binomen was nevertheless used. The presence of nematothecae is confirmed in Z. polycarpa Vervoort & Watson, 2003, a species with unusual gonothecae for the genus, now redescribed based on additional, abundant material. Zygophylax pseudosibogae Gu et al., 2022 is also redescribed, supplementing the original account. Finally, phylogenetic analyses, based on the 16S rRNA gene, allowed the genetic characterization of a total of twenty nominal species of Zygophylax, including sequences for eight taxa not considered so far. The number of Zygophylax species known from the New Caledonian area is raised from eight to sixteen.